Comparison of three different obstacle models for modeling of stratified flows over the body - Beneš, Luděk; Fraunié, Philippe (Proceedings of the Conference Algoritmy, 2015)
The article deals with the numerical simulation of the stratied incompressible  ows over the body. The mathematical model is based on the Boussinesq approximation of the Navier{ Stokes equations for viscous incompressible stratied  ow. Three dierent numerical approaches to the body are implemented and tested. The rst one is the classical body tted mesh. The second one is the penalization technique. The obstacle is modeled as the permeable obstacle with high resistance parameter. The last approach is based on the immersed boundary method. The resulting set of PDE's is then solved by the AUSM MUSCLE scheme in nite volume approximation. For the time integration the three stage BDF method of the second order is used.